Community-engaged performance tours : a guide for ensemble directors - Spinazzola, James (Routledge, 2024)
"Community-Engaged Performance Tours addresses the role of performance touring as a form of classroom and community engagement. Performance tours have long been a part of the collegiate and high school music ensemble experience, bringing student bands, choirs, and orchestras into connection with a wide variety of audiences, venues, and cultural contexts. This book presents a new approach to the performance tour that integrates touring with community engagement and service-learning. Emphasizing reciprocity, cross-cultural exchange, and global awareness, the author addresses how visiting ensembles can work with host communities instead of performing for them. The book includes student and community perspectives and case studies from the author's experience leading university wind symphony tours in Haiti and the Dominican Republic, and provides a practical and hands-on model for ensemble leaders and educators"--